Medico-legal litigation in Obstetrics: a characterization analysis of a decade in Portugal - Ana Patrícia Rodrigues Domingues; Adriana Belo; Paulo Moura; Duarte Nuno Vieira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSE: It was to analyse the most critical areas in Obstetrics and to suggest measures to reduce or avoid the situations most often involved in these disputes. METHODS: Obstetrics cases submitted to the Medico-legal Council since the creation of the National Institute of Legal Medicine and Forensic Sciences in 2001 until 2011 were evaluated. A comprehensive characterization, determination of absolute/relative frequencies, hypothesis of a linear trend over the years and the association between each parameter was done. RESULTS: The analysis has shown no significantly linear trend. The most common reasons for disputes were perinatal asphyxia (50%), traumatic injuries of the newborn (24%), maternal sequelae (19%) and issues related to prenatal diagnosis and/or obstetric ultrasound (5.4%). Perinatal asphyxia showed no significantly linear trend (p=0.58) and was usually related to perinatal deaths or permanent neurologic sequelae in newborn children. Traumatic injuries of the newborn, mostly related to instrumented deliveries, shoulder dystocia or vaginal delivery in breech presentation, has shown a significantly increased linear trend (p<0.001), especially related to instrumented deliveries. The delay/absence of cesarean section was the clinical procedure questioned in a significantly higher number of cases of perinatal asphyxia (68.7%) and of traumatic lesions of the newborn due to instrumented deliveries (20.5%). CONCLUSION: It is important to improve and correct theoretical/practical daily clinical performance in these highlighted areas, in order to reduce or even avoid situations that could end up in medico-legal litigations.